Sanctification and Migration Across Generations: Expanding the Explicit Curriculum of Asian American Discipleship - Law, Easten (2024)
How do migration experiences passed down across generations relate to God’s work of sanctification, and how might Asian American churches engage the stories of their ancestors as a form of Christian formation? Drawing from scripture, migration theologies, educational theory, literature in Asian American ministry, and personal experience, this article argues that Asian American churches must begin designing discipleship curriculum that explicitly honors, integrates, and embodies the stories of their families’ multiple migrations into their spiritual lives because it is through such remembrance and learning that God can render Christ-like transformation.
Keywords: Curriculum; Migration; Discipleship; Sanctification; Asian American Christianity